2012
DOI: 10.1016/j.ygyno.2011.12.315
|View full text |Cite
|
Sign up to set email alerts
|

Metformin targets ovarian cancer stem cells in vitro and in vivo

Abstract: Purpose-Studies in non-gynecologic tumors indicate that metformin inhibits growth of cancer stem cells (CSC). Diabetic patients with ovarian cancer who are taking metformin have better outcomes than those not taking metformin. The purpose of this study was to directly address the impact of metformin on ovarian CSC. Methods-The impact of metformin on ovarian cancer cell line growth and viability was assessed with trypan blue staining. Aldehyde dehydrogenase (ALDH) expressing CSC were quantified using FACS®. Tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 13 publications
1
12
0
Order By: Relevance
“…Several in vitro and in vivo pre-clinical investigations have detected a growth-static effect of metformin also in gynecological malignancies, including ovarian cancer (40,(48)(49)(50)(51)(52)(53)(54)(55), endometrial cancer (23-25, 55, 59-65, 67, 72, 74, 89) and breast cancer (12,17,22,38,130,131,134,135), mainly due to the effects of drug on the IGF system and different intracellular signaling transduction pathways .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several in vitro and in vivo pre-clinical investigations have detected a growth-static effect of metformin also in gynecological malignancies, including ovarian cancer (40,(48)(49)(50)(51)(52)(53)(54)(55), endometrial cancer (23-25, 55, 59-65, 67, 72, 74, 89) and breast cancer (12,17,22,38,130,131,134,135), mainly due to the effects of drug on the IGF system and different intracellular signaling transduction pathways .…”
Section: Discussionmentioning
confidence: 99%
“…Recent in vitro and experimental data suggest that metformin electively targets cancer stem cells [CSC]s, and acts together with chemotherapy to block tumor growth in different cancers, such as breast cancer , prostate cancer, lung cancer, and ovarian cancer (38)(39)(40).…”
Section: Antineoplastic Activity Of Metforminmentioning
confidence: 99%
“…Metformin, an oral biguanide medicine widely used for type 2 diabetes treatment, inhibited growth and survival of tumor cells and tumor stem cells in multiple malignances, which has been reported in numerous studies [18,[22][23][24][25][26]34]. In our study, we used OS MG63 cell line to examine the effects of metformin on osteosarcoma cell growth, migration, and invasion in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicate that metformin may reduce the risk of cancer in patients with type 2 diabetes [19][20][21]. Furthermore, in vivo and in vitro studies have demonstrated that metformin inhibits tumor cells and tumor stem cell growth and survival in numerous tumors [22][23][24][25][26]. Metformin induces the LKB1-mediated activation of AMPK which in turn inhibits mammalian target of rapamycin (mTOR) signaling and then affects protein synthesis and proliferation in various cancer cell lines [27].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, metformin intake has been shown to reduce ovarian cancer related mortality. It has also been shown that metformin enhances the chemo-sensitivity of patients with ovarian cancer [7][8][9]. However, the mechanism underlying the anticancer effects of metformin in the ovarian cancer cells is not fully understood.…”
Section: Introductionmentioning
confidence: 99%